2017
DOI: 10.1159/000467400
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Decline of Kidney Function in Human Immunodeficiency Virus-Infected Patients Under Routine Clinical Management

Abstract: Background: Since the introduction of antiretroviral therapy (ART), human immunodeficiency virus (HIV)-infected patients have a drastically improved prognosis but at the same time they are also more affected by non-HIV related complications, such as chronic kidney disease. The objective of our study was to investigate the effect of proteinuria and tenofovir (TDF)-containing ART regimens on the temporal evolution of estimated glomerular filtration rate (eGFR). Methods: Between April 2008 and October 2012, we en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Therefore, renal insufficiency could be the underlining cause of proteinuria arising from an advanced stage HIV infection and a declined CD4 count [ 20 22 ]. Conversely, some studies found no significant association between renal failure and a decline in CD4 count under routine clinical management [ 23 ]. There is no clear mechanism linking a declined CD4 count to the presence of hematuria in HIV infection; however, this could be attributed to unforeseen cofounders [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, renal insufficiency could be the underlining cause of proteinuria arising from an advanced stage HIV infection and a declined CD4 count [ 20 22 ]. Conversely, some studies found no significant association between renal failure and a decline in CD4 count under routine clinical management [ 23 ]. There is no clear mechanism linking a declined CD4 count to the presence of hematuria in HIV infection; however, this could be attributed to unforeseen cofounders [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%